The Effect of Digital Marketing and Human Resource Competency on the Performance of Fashion SMEs in Bandung City with SME Empowerment Through SME Digitalization Training as a Moderating Variable - Yohana Hutajulu; Sulaeman Rahman Nidar; Elnovani Lusiana (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to analyze the effect of digital marketing and human resource competencies on the performance of fashion MSMEs in Bandung City with MSME empowerment through MSME digitalization training as a moderating variable. A quantitative approach was used involving 160 respondents who are MSME players in the creative industry sector in the fashion sector registered at the West Java Province Cooperative and SME Office. The variables studied include digital marketing and human resource competencies as independent variables, MSME empowerment through MSME digitalization training as moderation, and MSME performance as the dependent variable. Data were collected through questionnaires and analyzed using the SEM-PLS (Structural Equation Modeling - Partial Least Squares) method. This study found that digital marketing can help improve the performance of MSMEs in the fashin sector in Bandung City, human resource competency variable as measured by skills, knowledge, abilities and education level can affect the performance of MSMEs in the fashin sector in Bandung City, MSME digitization training organized by the West Java Province Cooperative and SME Office can help fashion MSME entrepreneurs in Bandung City, and the effect of Human Resource Competencies on MSME Performance, the MSME Digitalization Training variable is not needed.